Nigeria : Health, Nutrition, and Population, Country Status Report, Volume 2, Main Report - World Bank (Washington, DC, 2012)
Nigeria's sheer size and complexity present large challenges to health policymakers. Not only is the population large, but it is also very diverse: there are nearly 300 ethnic groups in the country, more than 500 languages, and two major religious groups (Islam and Christianity). This complexity is mirrored by widely varying patterns of health outcomes and health services. Nigeria's federal system assigns different health system responsibilities to the three levels of government, each of which is largely autonomous in terms of management and financing despite national policies that provide a certain measure of standardization. Weak governance has been an obstacle to improving public services, including health care, although the democratic government is pursuing vigorous reforms. High dependency on oil revenue and poor economic management has resulted in volatility and uncertainty in the level of public resources. However, economic growth and better macroeconomic and fiscal policies have improved the situation in the past few years. Nonetheless, poverty -- one of the determinants of both health outcomes and health service use -- is widespread and inequalities -- that is, large urban-rural disparities and regional equalities -- loom large, translating into disparities in health outcomes and access to health services. It is within this context that this report analyzes the health situation of the poor in Nigeria and the performance of the health system in meeting the needs of the poor. The report has six chapters focusing on health outcomes, household behavior and community factors affecting health, health system and policy, the role of the private sector in health care provision, health care financing, and extra resources needed to achieve the health-related Millennium Development Goals.